The Effect of Communicative Language Teaching (CLT) on Students’ Speaking Ability at SMPN 1 Bengkalis - - Ervina; - Kurniati (STAIN Bengkalis, 2019)
The main aim of this research is to investigate the useful strategy in teaching and learning process to improve Speaking Ability at SMPN 1 Bengkalis at the seventh year. In this research, a researcher tries to modify Communicative Language Teaching (CLT) Using Video Technique into English material. The researcher uses Quasi-exprimental design which a data is taken from pre-test and post-test after giving a treatment for expriment group and non treatment for control group. The population and the sample of this research are the seventh grade of SMPN 1 Bengkalis in Bengkalis subdistric, the research is held for 6 (Six) meetings or 3 (Three) weeks. The research is quantitative, the data analysis of students’ performance in a pre and post-test, the result findings showed that students showed some improvement in Speaking Ability. It can be seen from the test scores after intervention compared to the control group. It means that there is significant effect of Communicative Language Teaching (CLT) Technique on Students’ Speaking Ability.